Ultrasound guided hydrostatic enema reduction of acute intussusception: guidelines in therapy and review of the institutional experience - Sarma, Vivek Parameswara (International Journal of Contemporary Pediatrics, 2020)
Background: In this review, author analyzed the cases of Acute Intussusception that underwent Ultrasound guided hydrostatic reduction during a one-year period. Author reviewed this treatment protocol and guidelines of non-operative and surgical therapy. The procedure followed and guidelines of therapy were reviewed and are detailed in the study. Methods: Retrospective analysis of the hospital data of all patients who were treated for acute Intussusception during the period of January 2017 to December 2017 was done. All records including admission data, investigations, procedure records, preoperative details and operation notes, where applicable, post procedure recovery data and incidence of recurrence were studied. Inclusion criteria included confirmed sonological diagnosis of Intussusception verified by the treating paediatric surgeon, availability of all necessary records and absence of other co-morbidities. Exclusion criteria included age more than 2 years, children who had other major systemic disease, doubtful sonological diagnosis and postoperative intussusception. The paediatric surgeon himself performed the procedure in the dedicated ultrasound suite. Results: The study was done in the mother and child wing of a medical college which is a tertiary referral centre catering to more than 200 cases of Intussusception per year. The records of 194 cases of Intussusception were available for analysis, of which only 176 could be included in the study. The age group included is 3 months to 3 years. The mean age was 11 months. The sex incidence was 94 cases in males and 82 in females. Conclusions: Ultrasound guided hydrostatic reduction is a safe, effective and convenient modality for treatment of acute Intussusception, which can be performed by the treating Paediatric surgeon himself with requisite training and exposure.